Wits appraisal study: 100 cephalometric analyses of Chinese teenagers (Bangladesh Journal of Dental Research & Education, 2013)
A cross sectional study was carried out within the lateral cephalograms on 100 Chinese teenage patients at the department of orthodontia in the second affiliated hospital of Dalian Medical University, CHINA in order to evaluate the Wits measurement as compared to ANB angle for identifying the anteroposterior skeletal discrepancy between maxilla & mandible and to determine the normal Wits value suitable for Caucasian descent whether it was applicable or not on the Chinese teenagers distributed according to sex, age & malocclusion variations. Non probability (purposive) sampling technique to collect 100 samples of lateral cephalometric radiographs and data were collected from the measurements of multiple planes & angles formed by adjoining various anatomic landmarks connecting to each other in those radiographs. Lateral cephalograms of those 100 subjects were divided according to gender, age & malocclusion type. In the sex group there were 43 males & 57 females. In the age group 68 patients ages were from 13 to 15 years and 32 patients ages were from 16 to 19 years. In the malocclusion group 41 patients had class I, 40 patients had class II & 19 patients had class III malocclusions. Statistical analyses were done by t-test (two independent samples) to detect the differences between two sex groups and also between the two age groups. One way ANOVA (analysis of variance) was applied to evaluate the differences of malocclusion classification. The results were statistically significant when p